2016
DOI: 10.2967/jnumed.115.168179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preclinical Evaluation of11C-UCB-J as a PET Tracer for Imaging the Synaptic Vesicle Glycoprotein 2A in the Brain

Abstract: The synaptic vesicle glycoprotein 2A (SV2A) is found in secretory vesicles in neurons and endocrine cells. PET with a selective SV2A radiotracer will allow characterization of drugs that modulate SV2A (e.g., antiepileptic drugs) and potentially could be a biomarker of synaptic density (e.g., in neurodegenerative disorders). Here we describe the synthesis and characterization of the SV2A PET radiotracer 11 C-UCB-J ((R)-1-((3-( 11 C-methyl-11 C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyrrolidin-2-one) in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
267
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(298 citation statements)
references
References 28 publications
19
267
0
Order By: Relevance
“…Other PET tracers based on 11 C-labeling have been also recently developed in preclinical species, e.g. [ 11 C]UCB-A [77] and [ 11 C]UCB-J [78]. As with UCB-H, UCB-J [( R )-1-((3-(methyl- 11 C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyrrolidin-2-one] is a heterocyclic non-acetamide compound [74].…”
Section: The Role Of Sv2a In Modulating Neuronal Excitability In the mentioning
confidence: 99%
See 2 more Smart Citations
“…Other PET tracers based on 11 C-labeling have been also recently developed in preclinical species, e.g. [ 11 C]UCB-A [77] and [ 11 C]UCB-J [78]. As with UCB-H, UCB-J [( R )-1-((3-(methyl- 11 C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyrrolidin-2-one] is a heterocyclic non-acetamide compound [74].…”
Section: The Role Of Sv2a In Modulating Neuronal Excitability In the mentioning
confidence: 99%
“…As with UCB-H, UCB-J [( R )-1-((3-(methyl- 11 C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyrrolidin-2-one] is a heterocyclic non-acetamide compound [74]. Its whole body biodistribution was studied in non-human primates, demonstrating high uptake and fast kinetics in the brain [78]. Preblocking with levetiracetam 10 and 30 mg/kg resulted in approximately 60 and 90 % occupancy, respectively.…”
Section: The Role Of Sv2a In Modulating Neuronal Excitability In the mentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET) can be used noninvasively to determine drug target engagement and occupancy in living subjects. Several PET radioligands have recently been developed for imaging of SV2A, with 11 C‐UCB‐J being considered best in class thus far . We previously demonstrated that 11 C‐UCB‐J binding could be displaced by intravenous infusion of BRV (5 mg/kg) or LEV (30 mg/kg) in nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by radiotracers selective to synaptic vesicle glycoprotein SV2A, a transmembrane protein expressed ubiquitously in secretory vesicles in all brain areas . Arising from several structural scaffolds related to the antiepileptic drug levetiracetam (LEV, 1 ; Figure ) the carbon‐11 radiolabelled UCB‐J analogue ([ 11 C] 2 ; Figure ) has been shown to have excellent in vitro and in vivo properties for imaging SV2A from both preclinical and clinical studies …”
Section: Introductionmentioning
confidence: 99%